INFRASTRUKTUR TEKNOLOGI INFORMASI (ITI) PADA PERUSAHAAN E-COMMERCE TOKOPEDIA - Fenny Purwani; Muhammad Rifky Andreawan; Muhammad Indra Irillah; Muhammad Farhan; Rama Antonius (Jurnal Riset Sistem Informasi, 2025)
This study aims to observe and analyze the information technology infrastructure (ITI) utilized by the e-commerce company Tokopedia, in order to understand the role of ITI in supporting operations and business development in the digital era. The research method employed includes literature review and indirect observation through the analysis of secondary data sources, such as articles, company reports, and online publications related to Tokopedia's technology systems. The analysis focuses on hardware, software, networks, data, and human resources components within the ITI system. The results indicate that Tokopedia possesses a robust ITI, based on cloud computing and microservices architecture, which supports scalability, security, and operational efficiency. The implementation of technologies such as big data, artificial intelligence, and API integration are key to enhancing user experience and internal effectiveness. The study concludes that Tokopedia's success in delivering reliable e-commerce services largely depends on its adaptive and integrated IT infrastructure, as well as continuous investment in technology development and human capital. This research highlights the strategic importance of ITI in enhancing competitiveness and innovation in the e-commerce industry.